Farmer perceptions of Imazapyr Resistant (IR) maize on the control of Striga in Western Kenya - Manyong, Victor M.; Nindi, S.J.; Alene, Arega D.; Odhiambo, G.D.; Omanya, G.; Mignouna, Hodeba D.; Bokanga, M. (2008)
For a long time, farmers in Nyanza and Western provinces in Kenya have had to deal with the Striga problem. To most of them Striga had become a way of life and they had given up hope. Striga affects their mainstay crops, which are maize, sorghum and mil- let. After an extensive search for a solution, IR maize was developed. However, like all new technologies, there is usually suspicion especially from the end user. A study was therefore conducted to find out the level of adoption and perception of farmers on this technology. This study also sought to identify the constraints in the deployment of this technology and arrest them on time. This report presents the findings of this study. The stratified random sampling method was used to select 10 districts, 16 sub- locations, 32 villages and 834 households. Two groups of farmers were investigated: baseline and WeRATE farmers defined on the basis of number of years of experience with IR maize. A combination of techniques for data collection was used, including literature review, interview of individual households and GPS recordings. Descriptive statistics (frequency of events and means of parameters) were applied for data analysis. Similarly, a binomial probit model was used to identify factors driving the perception of the various households on the IR maize technology. Findings from sampled households depict that most household heads are male. There were about 26% of households headed by females. The level of education was low for the heads of households and other members of farm families. Group membership was high especially among women. Most households (89%) had received extension visits while 68% had attended field days, seminars and/or agricultural shows. Farming activities were found to provide a substantial amount of income to most households. Maize is the major food crop and a source of cash income to most households. Farmers grow both local and improved (hybrid) maize varieties, but the productivity of maize is low. There is a considerable gap between potential and actual maize yields. Major factors constraining maize production include Striga infestation, drought, erratic rainfall and low soil fertility. Striga is by far the major threat to livelihoods of smallholders. Traditional methods of Striga control which include uprooting, burning and manuring have proved to be ineffective. Although alternative technologies exist, they have not been highly adopted and used, possibly because of lack of awareness. Awareness of Striga and Striga control technologies was substantial among sampled households. All were aware of IR maize technology followed by traditional practices, and push-pull; the least known technology of Striga control was the intercropping of legumes followed by cassava/Desmodium. Extension agents from the Ministry of Agriculture and local NGOs were found to be the leading sources of information and demonstrations on various Striga control technologies, including instructions/ guidelines required before the application of IR maize technology. x Farmers’ assessment of maize yields under different Striga control technologies revealed that maize yields were higher where farmers used IR maize and push-pull technologies. The least maize yields were observed in fields under traditional Striga control technologies. Likewise, IR maize technology was superior in reducing Striga population in the fields and control of both biotic and abiotic factors. There were also some implications to the introduction of IR maize technology such as change in weeding times, capital requirement, carefulness in handling farming activities and social implications such as group formation and emergency of credit societies. The study identified critical ways to speed up the adoption of IR maize technology. The need to establish proper diffusion channels was suggested as an important component before full deployment of this technology. The need to bring IR maize seeds to stock- ists near to farmers, increase cultivated plots to IR maize and increase IR maize kit and more extension on the technology were highlighted as some of the ways to scale-up the IR maize technology in the region. Other factors that contribute to the positive perception of IR maize, thus to its diffusion and adoption, are farmer perceptions on agronomy attributes of the technology, the number of extension visits, the exposure to the technology, and the responsiveness of the technology to farmer needs.